Improving The Diagnostic Accuracy of Exercise Stress Testing in Detecting Coronary Heart Disease using St/Hr Hysteresis - Suryaguna, I Made Sakta; Wiryawan, I Nyoman (Syntax Corporation Indonesia, 2026)
Coronary heart disease (CHD) is still the leading cause of cardiovascular morbidity and mortality in the world, including in Indonesia. Cardiac test with electrocardiography (ECG) is a widely used non-invasive test because it is relatively low cost and easy to perform, but the standard parameter of ST segment depression has limitations in diagnostic accuracy. ST/HR hysteresis is an alternative parameter that considers changes in the ST segment to heart rate during the exercise and recovery phases, which are reported to have better diagnostic capabilities. This study aims to assess the improvement of the diagnostic accuracy of cardiac training tests in detecting CHD using ST/HR hysteresis. This study is a diagnostic study conducted at Sanglah Hospital Denpasar in the period of December 2018 to April 2019. The subjects of the study were patients with suspected CHD who had undergone cardiac training tests and coronary angiography as the gold standard. The analysis was carried out on the ST/HR value of hysteresis obtained from secondary data, then the optimal cut-off point was determined using Receiver Operating Characteristic (ROC) analysis. A total of 134 patients were analyzed, with 59 patients (44%) proven to have significant CHD based on coronary angiography. The results of ROC analysis showed the cut-off point of ST/HR hysteresis ≥0.026 mV with an AUC value of 84.8%, sensitivity of 79.7%, and specificity of 85.3%. This value is higher than the variable parameters of the conventional ST segment. The net reclassification improvement (NRI) analysis showed a value of 0.28, which indicates an increase in diagnostic accuracy. It is concluded that ST/HR hysteresis improves the diagnostic accuracy of cardiac training tests and can be used as an effective and efficient additional parameter in detecting coronary heart disease.